Platform for Techno-economic Analysis of Fouling Mitigation Options in Refinery Preheat Trains - Ishiyama, E. M; Paterson, W. R; Wilson, D. I (Energy & fuels, 2009)
The rise in energy prices has increased interest in improving the efficiency of heat-transfer systems, particularly for the heat exchangers in crude oil preheat trains. Fouling in heat exchangers can result in reduced throughput, extra fuel consumption, or the imposition of limits on the operation of distillation columns. There are several mitigation options available, ranging from chemical (e.g., use of anti-fouling chemicals) to capital (new units, inserts, or configurations). Selecting the best option requires a techno-economic analysis of the performance of the preheat train before and after modification. This requires simulation to quantify the impact of molecular processes on unit performance and plant economics. We present examples of the use of a new simulation tool, incorporating the impact of fouling on the heat transfer in and throughput of preheat trains. We examine dynamic phenomena, such as pump performance, flow splits across parallel sets of heat exchangers, and fouling rates dependent upon temperature and flow. The versatility of the tool is demonstrated by calculating optimal cleaning operations for a representative preheat train subject to fouling under (a) different energy and crude costs and (b) impact of different fouling rates (e.g., simulating the use of chemical mitigation). We shall also demonstrate application of the tool to assess the consequences of column revamps.